Simulation and optimal control of crude oil separation process at offshore facilities to improve efficiency of oil and condensate recovery / Chin Yee Kai - Chin, Yee Kai (2020)
Crude oil separation process is the most crucial process in offshore production facilities in ensuring the well fluid is separated efficiently and persistently. Waxy crude or sluggish feed stream is the major disturbance that could cause operational issues and production loss due to process upset. The main objective of this research is to model offshore crude oil separation process and introduce state space control to optimize the control of total liquid and water level within the permissible range as well as to evaluate the effect of disturbances to the controls. This work presents two different modelling methods in developing three-phase separator model and application of state space control in optimizing the level control. The three-phase separator model is developed for liquid level and water phase level control using mathematical modelling and data driven modelling method via HYSYS. The mathematical model is based on two dynamic state equations representing the levels of the liquid and water and gas pressure with inflow and outflow dynamics. HYSS is used to simulate the three-separator dynamic process in a more realistic environment. The dynamic responses of liquid and water level to the command input of respective control valves are used to obtain data that is required to develop state space model. Application of state space (modern) control which are the feedback, feedforward control and integral action is investigated and evaluated in terms of its performance in controlling outflows of the separator in optimizing control of the separation process as well as in rejecting various disturbances such as slugging. In the end of this research, the simulation results show that state space control is able to control the crude oil separation process as desired while rejecting disturbances without causing process upsets. It was also found that by implementing integral action control, fast response time and zero steady state error can be achieved indicating that in the meantime, process fluctuation can be minimized and system response faster whereby it would help to improve the overall separation process efficiency.